Does prehospital thrombolysis increase the proportion of patients who have an aborted myocardial infarction?. Issue 3 (20th February 2009) - Jackson, L; Kendall, J; Castle, N
Abstract : Background: An "aborted" myocardial infarction is defined as an acute coronary syndrome where there is rapid resolution of existing ST segment elevation associated with a rise in creatine kinase (CK) less than twice the upper limit of normal or a small troponin release compatible with minimal myocyte necrosis. Previous research has shown that earlier thrombolysis is associated with a higher rate of aborted infarction. It is also known that prehospital thrombolysis reduces the pain-to-needle time. Aim: To test the hypothesis that prehospital thrombolysis is associated with a higher incidence of aborted infarction in a UK setting. Methods: A retrospective analysis was performed for all patients given prehospital thrombolysis in the Avon sector catchment area of the Great Western Ambulance Service and Frimley Park Hospital between April 2004 and October 2006. The control group were patients given in-hospital thrombolysis at Frenchay Hospital or Frimley Park Hospital over the same period. Data reporting 12 h troponin levels, call-to-needle time, pain-to-needle time, door-to-needle time and incidence of aborted infarction were collected. Results: Of the patients receiving prehospital thrombolysis, 69% had a pain-to-needle time of 2 h or less compared with 40.4% of patients receiving in-hospital thrombolysis (p<0.001). The overall incidence of aborted infarction was 16.5%. Of those with aborted infarction for whom pain-to-needle times were available, 54% had a pain-to-needle time of <2 h. Despite the difference in pain-to-needle times in favour of prehospital thrombolysis, there was no difference in the incidence of aborted myocardial infarction between the prehospital thrombolysis cohort and the in-hospital cohort, with 18.2% of in-hospital patients having a troponin I level <0.5 ng/ml compared with 11.8% of the prehospital cohort (p = 0.124). Conclusion: Although prehospital thrombolysis improved pain-to-needle time and a shorter pain-to-needle time increased the incidence of aborted infarction, prehospital thrombolysis was not associated with an increase in the proportion of aborted myocardial infarctions. Further work is required to understand this unexpected finding.